They say blue (Recorded Books, Inc., Abrams Books for Young Readers, 2018)
Caldecott Honor winner Jillian Tamaki's book They Say Blue is a playful, poetic exploration of color and point of view. A Boston Globe -Horn Book Picture Book Award Winner In captivating paintings full of movement and transformation, we follow a young girl through a year or a day as she examines the colors in the world around her. Egg yolks are sunny orange as expected, yet water cupped in her hands isn't blue like they say. But maybe a blue whale is blue. She doesn't know; she hasn't seen one. Playful and philosophical, They Say Blue is a book about color as well as perspective, about the things we can see and the things we can only wonder at.

My many colored days (A.A. Knopf, Distributed by Random House, Knopf, 1998)
Accompanying a manuscript Dr. Seuss wrote in 1973, was a letter outlining his hopes of finding "a great color artist who will not be dominated by me." The late Dr. Seuss saw his original text about feelings and moods as part of the "first book ever to be based on beautiful illustrations and sensational color." The quest for an artist finally ended--after the manuscript languished for more than two decades--at the paint brushes of husband-and-wife team Steve Johnson and Lou Fancher whose stunning, expressive paintings reveal such striking images as a bright red horse kicking its heels, a cool and quiet green fish, a sad and lonely purple dinosaur, and an angrily howling black wolf. Using a spectrum of vibrant colors and a menagerie of animals, this unique book does for the range of human moods and emotions what Oh, the Places You'll Go! does for the human life cycle. Here is a wonderful way for parents to talk with children about their feelings. With Johnson and Fancher's atmospheric, large-scale paintings bursting off the pages, Dr. Seuss's vision is brought to life. This rare and beautiful book is bound to appeal to both the innocent young and the most sophisticated seniors.

Red: a crayon's story ([Library Ideas, LLC], Greenwillow Books, HarperCollins, Scholastic, Inc, Greenwillow Books, an imprint of HarperCollinsPublishers, 2017)
A blue crayon mistakenly labeled as "red" suffers an identity crisis in this picture book by the New York Times-bestselling creator of My Heart Is Like a Zoo. This funny, heartwarming, colorful picture book about finding the courage to be true to your inner self can be read on multiple levels, and it offers something for everyone. Funny, insightful, and colorful, Red: A Crayon's Story is about being true to your inner self and following your own path despite obstacles that may come your way. Red will appeal to fans of Lois Ehlert, Eric Carle, and The Day the Crayons Quit, and makes a great gift for readers of any age! Red has a bright red label, but he is, in fact, blue. His teacher tries to help him be red (let's draw strawberries!), his mother tries to help him be red by sending him out on a playdate with a yellow classmate (go draw a nice orange!), and the scissors try to help him be red by snipping his label so that he has room to breathe. But Red is miserable. He just can't be red, no matter how hard he tries! Finally, a brand-new friend offers a brand-new perspective, and Red discovers what readers have known all along. He's blue!

Pinkalicious (Pinkalicious, 1, 1, 2006)
This sparkling New York Times bestselling picture book from Victoria and Elizabeth Kann celebrates all things pink while showing readers that being yourself is the best of all. This 10th anniversary edition of Pinkalicious features a special sticker and a glittery jacket just for the occasion. Pinkalicious loves all things pink. From fairy dresses to cotton candy to bubblegum. Most importantly she loves eating pink cupcakes. Mommy and Daddy warn her not to eat too many, but Pinkalicious can't help herself. They're just too good! But when Pinkalicious eats one too many, she turns pink herself! What will she do? Pinkalicious is the first picture book starring Pinkalicious and her family. She stars in five more picture books--Purplicious, Goldilicious, Silverlicious, Emeraldalicious, and Aqualicious--as well as I Can Reads, doodle books, and more!

Why do leaves change color? (Let's Read and Find Out Science 2, ,, 1994)
In clear text, this book explains the concepts of photosynthesis, pigments and chlorophyll. It also includes activities that children can do with leaves.

Green is for Christmas (Crayon books (Drew Daywalt), , 1, 2022)
In this Christmas story starring the crayons from the #1 New York Times bestseller The Day The Crayons Quit , Green Crayon is certain that he is the only Christmas color in the box. Of course, Red, White, Silver and even Tan have something to say about that... When Green Crayon claims that green is the only color for Christmas, other crayons let him know that there would be no Christmas without them either. No candy canes or Santa without Red, no snow without White, no bells or stars without Silver, and no cookies or reindeer without Tan! The crayons agree that they all need to come together to make Christmas special. This humorous, small hardcover Christmas story is the perfect stocking stuffer and a great gift for fans of The Day The Crayons Quit --and all kids who like to color.

The day the crayons came home (Crayon books (Drew Daywalt), , 1, 2015)
The companion to the #1 New York Times bestseller and blockbuster hit, The Day the Crayons Quit ! A Wall Street Journal Best Children''s Book of 2015 A TIME Magazine Top 10 Children''s Book of 2015 "Highly anticipated (yes, even for adults)" -- Entertainment Weekly I''m not sure what it is about this kid Duncan, but his crayons sure are a colorful bunch of characters! Having soothed the hurt feelings of one group who threatened to quit, Duncan now faces a whole new group of crayons asking to be rescued. From Maroon Crayon, who was lost beneath the sofa cushions and then broken in two after Dad sat on him; to poor Turquoise, whose head is now stuck to one of Duncan''s stinky socks after they both ended up in the dryer together; to Pea Green, who knows darn well that no kid likes peas and who ran away--each and every crayon has a woeful tale to tell and a plea to be brought home to the crayon box. Look for a special glow-in-the-dark picture [Note: make sure to "charge" it under a light first]. Praise for The Day the Crayons Came Home: Winner of the Goodreads Choice Award for Best Picture Book of 2015! A Wall Street Journal Best Book of 2015! One of Parents Magazine ''s Ten Best Children''s Books of 2015! A Publishers Weekly Best Book of the Year! "Funnier than the creators'' original blockbuster."-- Parents Magazine "Mr. Daywalt''s text blends with Mr. Jeffers''s illustrations to make a picture book that will have children clamoring for more crayon adventures."-- The Wall Street Journal "Continues its predecessor''s pleasing, goofy conceit...Once again, both Daywalt''s text and Jeffers'' illustrations are endearing."-- New York Times Book Review "By telling stories from the points of view of crayons, giving voices to the small and ignored, Daywalt and Jeffers have created two books that offer plenty of charm and fun, but also make children feel deeply understood."-- The Boston Globe * "A masterwork of humor and design . . . Sure to be as popular as The Day the Crayons Quit ."-- Booklist, starred review * "A brilliant, colorful tale that begs to be read aloud and a must-have for all collections."-- School Library Journal, starred review * "Once again, Daywalt and Jeffers create rich emotional lives and personalities for their colorful cast, and it''s hard to imagine a reader who won''t be delighted."-- Publishers Weekly , starred review "Not only stands on its own merit, but may be even more colorful than the original."-- Huffington Post "Drew Daywalt and Oliver Jeffers once again offer perceptive and frequently hilarious insights... The Day the Crayons Came Home will have readers of all ages chuckling--and will inspire kids'' empathy and imagination in equal measure." -- BookPage Praise for The Day the Crayons Quit: The #1 New York Times bestselling phenomenon -- over two years on the bestseller list! Winner of the E.B. White Read-Aloud Award Amazon''s 2013 Best Picture Book of the Year A Barnes & Noble Best Book of 2013 Goodreads'' 2013 Best Picture Book of the Year * "Hilarious . . . Move over, Click, Clack, Moo ; we''ve got a new contender for the most successful picture-book strike." - BCCB , starred review "Jeffers . . . elevates crayon drawing to remarkable heights." - Booklist "Fresh and funny." - The Wall Street Journal "This book will have children asking to have it read again and again." - Library Media Connection * "This colorful title should make for an uproarious storytime." - School Library Journal , starred review * "These memorable personalities will leave readers glancing apprehensively at their own crayon boxes." - Publishers Weekly , starred review "Utterly original." - San Francisco Chronicle

Purplicious (Pinkalicious, 2, 1, 2007)
It's purple Pinkalicious! Pinkalicious loves the color pink, but all the girls at school like black. They tease her, saying that pink stinks and pink is for babies. But Pinkalicious doesn't think so...that is, until her friends stop playing with her. Now Pinkalicious has a case of the blues. But could she ever turn her back on her favorite color In the follow-up to the bestselling Pinkalicious, a young girl remains true to herself and discovers that pink isn't only a pretty color, but also a powerful one.

The day the crayons quit (Crayon books (Drew Daywalt), , 1, 2015)
The hilarious, colorful #1 New York Times bestselling phenomenon that every kid wants! Gift a copy to someone you love today. Poor Duncan just wants to color. But when he opens his box of crayons, he finds only letters, all saying the same thing: His crayons have had enough! They quit! Blue crayon needs a break from coloring all those bodies of water. Black crayon wants to be used for more than just outlining. And Orange and Yellow are no longer speaking--each believes he is the true color of the sun. What can Duncan possibly do to appease all of the crayons and get them back to doing what they do best? With giggle-inducing text from Drew Daywalt and bold and bright illustrations from Oliver Jeffers, The Day the Crayons Quit is the perfect gift for new parents, baby showers, back-to-school, or any time of year! Perfect for fans of Don't Let the Pigeon Drive the Bus by Mo Willems and The True Story of the Three Little Pigs by Jon Sciezka and Lane Smith. Praise for The Day the Crayons Quit: Amazon's 2013 Best Picture Book of the Year A Barnes & Noble Best Book of 2013 Goodreads' 2013 Best Picture Book of the Year Winner of the E.B. White Read-Aloud Award * "Hilarious . . . Move over, Click, Clack, Moo ; we've got a new contender for the most successful picture-book strike." - BCCB , starred review "Jeffers . . . elevates crayon drawing to remarkable heights." - Booklist "Fresh and funny." - The Wall Street Journal "This book will have children asking to have it read again and again." - Library Media Connection * "This colorful title should make for an uproarious storytime." - School Library Journal , starred review * "These memorable personalities will leave readers glancing apprehensively at their own crayon boxes." - Publishers Weekly , starred review "Utterly original." - San Francisco Chronicle

Full spectrum: how the science of color made us modern (Houghton Mifflin Harcourt, HarperCollins, 2021)
"Informative and entertaining...Rogers is a seasoned raconteur, unreeling an eons-spanning tale with skill." --Wall Street Journal A lively account of our age-old quest for brighter colors, which changed the way we see the world, from the best-selling author of Proof: The Science of Booze From kelly green to millennial pink, our world is graced with a richness of colors. But our human-made colors haven't always matched nature's kaleidoscopic array. To reach those brightest heights required millennia of remarkable innovation and a fascinating exchange of ideas between science and craft that's allowed for the most luminous manifestations of our built and adorned world. In Full Spectrum, Rogers takes us on that globe-trotting journey, tracing an arc from the earliest humans to our digitized, synthesized present and future. We meet our ancestors mashing charcoal in caves, Silk Road merchants competing for the best ceramics, and textile artists cracking the centuries-old mystery of how colors mix, before shooting to the modern era for high-stakes corporate espionage and the digital revolution that's rewriting the rules of color forever. In prose as vibrant as its subject, Rogers opens the door to Oz, sharing the liveliest events of an expansive human quest--to make a brighter, more beautiful world--and along the way, proving why he's "one of the best science writers around."* *National Geographic

Pete the Cat: I love my white shoes (Pete the cat picture books (James Dean), , 1, 2010)
Don't miss the first and bestselling book in the beloved Pete the Cat series! Pete the Cat goes walking down the street wearing his brand-new white shoes. Along the way, his shoes change from white to red to blue to brown to WET as he steps in piles of strawberries, blueberries, and other big messes! But no matter what color his shoes are, Pete keeps movin' and groovin' and singing his song...because it's all good. Pete the Cat: I Love My White Shoes asks the reader questions about the colors of different foods and objects--kids love to interact with the story. The fun never stops--download the free groovin' song. Don't miss Pete's other adventures, including Pete the Cat: Rocking in My School Shoes, Pete the Cat and His Four Groovy Buttons, Pete the Cat Saves Christmas, Pete the Cat and His Magic Sunglasses, Pete the Cat and the Bedtime Blues, Pete the Cat and the New Guy, Pete the Cat and the Cool Cat Boogie, Pete the Cat and the Missing Cupcakes, Pete the Cat and the Perfect Pizza Party, and Pete the Cat: Crayons Rock!

The crayons go back to school (Crayon books (Drew Daywalt), , 1, 2023)
The hilarious crayons from the #1 New York Times bestselling The Day The Crayons Quit are ready to go back to school! The crayons are getting ready to go back to school, and each crayon has a subject they're looking forward to the most. They're also ready to meet new friends. . . and let loose during their very favorite time of day: art class. A humorous, small hardcover back-to-school story from everyone's favorite school supplies.

The crayon box that talked (Random House Children's Books, Random House, Random House Children's Books, a division of Random House, Inc, 1997)
Yellow hates Red, so does Green, and no one likes Orange! Can these crayons quit arguing and learn to cooperate? Shane DeRolf's deceptively simple poem celebrates the creation of harmony through diversity. In combination with Michael Letzig's vibrant illustrations, young readers will understand that when we all work together, the results are much more colorful and interesting.

I went walking (Harcourt Brace big books, ,, 1990)
A child discovers a parade of animals in this picture book filled with playful humor and rhyme. This simple, funny read-aloud follows a boy's exciting stroll through the countryside. The boy sees a black cat, then a brown horse, then a red cow, and so on, and before he knows it, he's being trailed by the entire menagerie! Big type, repetition, lively art, and the visual guessing game created by introducing each animal only partially at first, make this beloved tale a winner at story time. I went walking. What did you see? I saw a black cat Looking at me.

Brown bear, brown bear, what do you see? (World of Eric Carle, ,, 2012)
With more than two million copies sold, Brown Bear, Brown Bear, What Do You See? has opened up a world of learning to a generation of children. For this edition, created for the twenty-fifth anniversay in 1992, Bill Martin, Jr., restored his text to its original wording. And Eric Carle created all new pictures--based on the originals, but clearer, brighter, and truer to the colors they represent. Bill Martin has been devoted to writing children's books for more than thirty years. He has a Ph.D. in early childhood education and he has long been a proponent of using rhyme and rhythm to teach young children how to read. Eric Carle, illustrator of many beloved children's books, was born in the United States, but spent his early years in Stuttgart, Germany, where he studied art and design at the Academy of Applied Art. Brown Bear, Brown Bear, What Do You See? was the first book he illustrated. This title has Common Core connections.

All the colors of the rainbow (Rookie read-about science, ,, 1998)
Explains how rainbows are formed by the colors in sunlight shining through water.

What's your favorite color? (Eric Carle and friends' what's your favorite, 2, 1, 2017)
Everybody has a favorite color. Some like blue balloons or brown buildings or mint green ice cream cones. Others prefer sunshine yellow, Maine morning gray, or Mexican pink. In What's Your Favorite Color? , fifteen beloved children's book artists draw their favorite colors and explain why they love them. This personal collection will undoubtedly inspire readers to create favorite color drawings and stories of their own! Contributors include: Eric Carle, Lauren Castillo, Bryan Collier, Mike Curato, Etienne Delessert, Anna Dewdney, Rafael Lopez, William Low, Marc Martin, Jill McElmurry, Yuyi Morales, Frann Preston-Gannon, Uri Shulevitz, Philip C. Stead, Melissa Sweet

Where can art take you? (Scholastic, 2013)
Introduces readers to the basics of art, including the primary colors.

Color (Gale, 2010)
Description Not Provided

Pete the Kitty and the unicorn's missing colors (Pete the kitty, , 1, 2020)
A magical unicorn adventure from New York Times bestselling creators Kimberly and James Dean! Pete the Kitty's friend Stevie the unicorn somehow lost all the colors in her rainbow tail. It's a good thing Pete has his magical paintbrush to help out. Together, they search for the missing colors of the rainbow. Young unicorn fans will love Pete's enchanting adventure in this My First I Can Read story, complete with original illustrations from the creator of Pete the Cat, James Dean. My First I Can Read books are perfect for shared reading with a child. Books at this level feature basic language, word repetition, and whimsical illustrations, ideal for sharing with emergent readers. The active, engaging stories have appealing plots and lovable characters, encouraging children to continue their reading journey.